2010
DOI: 10.1002/app.32669
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on corrosion protection properties of polyimide‐silica and polyimide‐clay composite materials

Abstract: Comparative studies on corrosion protection properties of polyimide-silica-clay composites were studied in this article. A series of polyimide-silica (PIS), polyimide-clay (PIC), and polyimide-silica-clay composites (PISC) materials, consisting of an organo-soluble polyimide (ODA-BSAA) matrix, inorganic silica particles prepared through the sol-gel reaction of tetraethyl orthosilicate (TEOS) and dispersed nanolayers of inorganic montmorillonite clay, were successfully prepared by solution dispersion technique.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The intense peak at near 1020 cm −1 and the two bands at 472 and 529 cm −1 are assigned to SiO bonds' stretching and SiO bonds' bending, respectively for both samples . While the characteristic absorption bands of HSE are displayed at 2921 and 2851 cm −1 for CH stretching vibration, 1470 cm −1 for CN stretching .…”
Section: Resultsmentioning
confidence: 89%
“…The intense peak at near 1020 cm −1 and the two bands at 472 and 529 cm −1 are assigned to SiO bonds' stretching and SiO bonds' bending, respectively for both samples . While the characteristic absorption bands of HSE are displayed at 2921 and 2851 cm −1 for CH stretching vibration, 1470 cm −1 for CN stretching .…”
Section: Resultsmentioning
confidence: 89%
“…For example, Yeh and co-workers demonstrated that the incorporation of organophilic clay platelets into a polymer matrix, in the form of organic-based coatings, may effectively enhance the corrosion protection of polymers on metallic surfaces. [27][28][29][30][31][32][33][34][35][36][37][38] This is because of the good dispersion (intercalation and exfoliation, Fig. 18.2 ) of the plate-like clay platelets in the polymer matrix, which effectively increase the length of the diffusion pathways for oxygen and water.…”
Section: Anticorrosion Propertiesmentioning
confidence: 97%
“…Therefore, it is reasonable to assume that increasing the difficulty of the diffusion pathway will effectively prevent H 2 O and O 2 from accessing the substrate surface, leading to good anticorrosion properties of the coating. Recently, many studies have shown that nanofiller can effectively enhance the barrier properties of various polymers [14,[43][44][45][46]. This is because their morphologies have high aspect ratios that lengthen the diffusion pathways for moisture or oxygen, leading to improved barrier properties [47,48].…”
Section: Barrier Properties Of Pi Nanocomposite Filmsmentioning
confidence: 99%